The Relation between Postvoid Residual and Occurrence of Urinary Tract Infection after Stroke in Rehabilitation Unit - Kim, Bo-Ram (Korean Academy of Rehabilitation Medicine, 2012)
OBJECTIVE: To determine the relation between postvoid residual (PVR) and the occurrence of urinary tract infection (UTI) in stroke patients. METHOD: One hundred and eighty-eight stroke patients who were admitted to an inpatient rehabilitation unit and who did not have UTI on admission (105 males, 83 females, mean age 67.1 years) were included in this study. The PVR was measured 3 times within 72 hours after admission. Mean PVR, demographic variables, K-MMSE (Korean Mini-Mental State Examination), initial K-MBI (Korean Modified Barthel Index), Foley catheter indwelling time and stroke type were defined and the relation to the occurrence of UTI was analyzed. RESULTS: UTI occurred in 74 patients (39.4%) during admission to the rehabilitation unit. There were significant differences between the UTI and non-UTI groups in K-MMSE, K-MBI, Foley catheter indwelling time (p<0.01). However, age, gender, stroke location and type were not associated. The occurrence of UTI was 4.87 times higher in the patients with a mean PVR over 100 ml than in those with a mean PVR <100 ml. The mean PVR was 106.5 ml in the UTI group, while it was 62.7 ml in the non-UTI group (p<0.01). PVR was not associated with age. CONCLUSION: The UTI rate is higher when the mean PVR is over 100 ml irrespective of gender and age. Close monitoring of PVR and appropriate intervention is needed to reduce the occurrence of UTI in stroke patients.